Phosphorus Removal from Water and Waste Water by Chemical Precipitation Using Alum and Calcium Chloride - A. M. Mohammed, Sawsan; Abbas Shanshool, Haider (Iraqi Journal of Chemical and Petroleum Engineering, 2009)
Phosphorus is usually the limiting nutrient for eutrophication in inland receiving waters; therefore, phosphorus concentrations must be controlled. In the present study, a series of jar test was conducted to evaluate the optimum pH, dosage and performance parameters for coagulants alum and calcium chloride. Phosphorus removal by alum was found to be highly pH dependent with an optimum pH of 5.7-6. At this pH an alum dosage of 80 mg/l removed 83 % of the total phosphorus. Better removal was achieved when the solution was buffered at pH = 6. Phosphorus removal was not affected by varying the slow mixing period; this is due to the fact that the reaction is relatively fast.The dosage of calcium chloride and pH of solution play an important role in phosphorus removal. The removal efficiency increases with increasing pH, and the optimum dosage of CaCl2 was 60 mg/l. Alum demonstrated much better results in phosphorus removal than CaCl2.